Sunlight-driven photocatalytic per- and polyfluoroalkyl substances degradation over zinc oxide/cellulose nanofiber catalyst using a continuous flow reactor. Issue 6 (December 2022) - Dehghani, Mostafa; Naseri, Mahdi; Nadeem, Humayun; Banaszak Holl, Mark M.; Batchelor, Warren
Abstract: Recalcitrant pollutants in water with high resistance to natural degradation such as per/polyfluoroalkyl substances (PFAS) highlight the need for sustainable, cheap, and effective treatment approaches. Although photocatalysis under direct sunlight can be beneficial due to the usage of ambient conditions for the reaction, air as the oxidant, and sunlight as the energy source, identifying sustainable and sunlight photoactive materials and a process that is both scalable and industrially feasible are challenging. Herein, we report the use of ZnO/cellulose nanofiber (CNF) composites for the photodegradation of PFOA and PFOS upon irradiation by sunlight in a continuous flow photoreactor. HPLC/MS/MS and fluoride quantification using the SPADNS method were used to track the degradation of PFAS and by-product formation. Aqueous solutions of three different standard PFAS samples containing 1200 µg/L of PFOA, 800 µg/L PFOS, and a mixture of 900 µg/L of PFOA and 900 µg/L of PFOS, and a wastewater treatment plant sample with 2.5 µg/L of an environmental mixture of PFAS compounds present in urban wastewater were used for the photocatalytic degradation tests. The concentration of these pollutants and their by-products in these samples was reduced to 0.5 µg/L, 0.07 µg/L, 0.15 µg/L, and 0.3 µg/L with an EE/O figure of merit of 0.19, 0.28, 0.43, 0.88 kWh/m 3 per order, respectively. It was observed that the standard mixture and the wastewater treatment plant samples were harder to degrade as compared to the standards containing one PFAS compound. Reusing the catalyst for three cycles showed less than 4% reduction in photodegradation over irradiation time. These findings emphasize the importance of location-specific design as the choice of photocatalyst is enabled by the UVA/B solar radiance characteristics present in Australia. Graphical Abstract: Synopsis: This study presents a sun-flow apparatus for the photocatalytic degradation of PFAS in sample water and wastewater and bringing down its and its by-products concentrations below the limits advised by EPA and WHO. Photocatalytic degradation of low concentration PFAS persistent organic pollutants in water using a novel sunlight-driven, continuous flow process. ga1 Highlights: Sun-flow photocatalytic PFASs degradation was investigated. photodegradation of real wastewater containing PFASs was studied. For the photodegradation process, zinc oxide/cellulose nanofiber catalyst was used. The concentration of pollutants was reduced to below advised limits.